Decomposition of Maize Straw between Two Phosphate Solubilizing Fungi: Aspergillus Niger and Penicillium Chrysogenum - Wang Liyan (E3S Web of Conferences, 2022)
Aspergillus niger (A. niger) and Penicillium chrysogenum (P. chrysogenum) can significantly promote the degradation of maize straw and phosphorus release. Compared with P. chrysogenum, A. niger is more efficient in maize straw degradation and phosphorus releasing. After seven days of incubation, the highest degradation ratio and phosphorus content in A. niger+maize straw treatment is 2.58% and 2.3 mg/L, respectively. The mechanisms for maize straw decomposition between these two fungi are different. Oxalic acid is the primary organic acid secreted by A. niger, which is more function in the decomposition of maize straw compared with propionic acid secreted by P. chrysogenum. In addition, A. niger has higher acidic xylanase and lignin peroxidase enzymes activities, which is conducive to the degradation of more stable substances in maize straw, i.e., lignin. This study indicated that A. niger is the primary candidate for the reuse of crop straw in the way of return to the field.